Teaching English as a Foreign Language and Smarter Learning Environments in the New Age of Digital Transformation - Roozafzai, Zahra Sadat (Educational Challenges, 2024)
The fully online and electronic environments of today as the only way of teaching/learning require some reviews and appraisals of the paradigms of digital transformation, including the paradigm of smart education. Therefore, the current study investigated the paradigm change of the smart education to the smarter education, leading to the review of Teaching English as a Foreign Language (TEFL). Purpose. The current study intends to update both the traditional theories and practice of TEFL in the new age of digital transformation, which will have effective theoretical and empirical implications in the practice of TEFL in smarter learning environments. Methodology. The present study was designed in two phases and employed a qualitative methodology with a descriptive design. It tried to answer how this paradigm change affects the theories of TEFL. Results. In the first phase of the study, the Preliminary Framework for Smart Learning Environments by Spector was adapted and expanded into the Model of Smarter Learning Environments based on the challenges and opportunities brought about by the new age of digital transformation. The second phase involved reviewing Krashen’s Acquisition/Learning Hypothesis, exploring its relevance and applicability to TEFL in the context of the Model of Smarter Learning Environments. The aim of this phase was to identify the potential challenges and opportunities associated with managing TEFL classroom resources within this new framework. The investigation concluded that the mandatory application of fully online teaching, in the case of TEFL, which resulted from the New-Age Digital Transformation, requires reviewing the traditional theories of Second Language Learning and Teaching. It has created challenges and opportunities in the class resource management. Finally, providing digital facilities and training was proposed as a solution to the challenges.